Peranan Perpustakaan Dalam Proses Pendidikan: Berdasarkan Sudut Pandang Kepala Sekolah, Guru, Karyawan, Tenaga Perpustakaan, dan Siswa di SMA Negeri 1 Sungayang Kabupaten Tanah Datar - Putri, Hafiza; Nst., Bakhtaruddin (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
This paper aims to describe the development of the collection at the Library of SMA Negeri 1 Sungayang, analyze visits to the Library with librarian SMA Negeri 1 Sungayang, and to describe the efforts of library staff in increasing interest in a visit to the Library of SMA Negeri 1 Sungayang. From the data analysis it was found that: (1) building a collection of the Library of SMA Negeri 1 Sungayang not running optimally within the meaning of the collection has not been planned development on a regular basis, (2) visits to the Library librarian State sma 1 Sungayang relatively little on average only 21 6% per day during tahun2012, and (3) library staff efforts made to attract visitors to the Library of SMA Negeri 1 Sungayang (2) visits to the Library librarian SMA Negeri 1 Sungayang relatively little on average only 21.6% per day for tahun2012, and (3) library staff efforts made to attract visitors to the Library of SMA Negeri 1 Sungayang is to organize a library building to be attractive and comfortable place to visit, providing a new source of reading and in accordance with the requirements librarian, adequate facilities, and into force profetional library and library staff that is friendly to visitors. Of these findings are expected in future pay more attention to the principal collections of the Library, especially coaching SMA Negeri 1 Sungayang can be done on an ongoing basis and regularly. In addition, the library in order to run basic tasks and fugsion optimally, should libraries be managed by professional librarians library science background. Keywords: collection; user; professional; optimized, descriptions.